(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cerebral arteriovenous malformation (AVM) is a congenital anomaly of the brain’s vascular system characterized by the formation of abnormal tangles connecting arteries and veins. Cerebral AVMs, being highly complex entities for both neurologists and neurosurgeons, continue to attract considerable attention from researchers and clinicians alike, aiming to identify the most effective treatment strategies and to deepen the understanding of the underlying processes that govern the formation and progression of these vascular malformations.